The other victims : first-person stories of non-Jews persecuted by the Nazis - Friedman, Ina R. (Boston : Houghton Mifflin Co., 1990)
Personal narratives of Christians, Gypsies, deaf people, homosexuals, and blacks who suffered at the hands of the Nazis before and during World War II.
Includes bibliographical references (p. 206-207).
Keywords: World War, 1939-1945 -- Personal narratives -- Juvenile literature; World War, 1939-1945 -- Atrocities -- Juvenile literature; World War, 1939-1945 -- Participation, Juvenile -- Juvenile literature; World War, 1939-1945 -- Europe -- Juvenile literature; Persecution -- Europe -- History -- 20th century -- Juvenile literature; Youth -- Europe -- Biography -- Juvenile literature; Holocaust survivors; World War, 1939-1945 -- Personal narratives